PENGARUH KOMPENSASI, SEMANGAT KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA YAYASAN PONDOK PESANTREN ROUDLOTUT THOLIBIN BALEN BOJONEGORO - jurnalpps pps; Budi Utomo; Mei Indrawati; Hidayat ÔÇÄ (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
The purpose of this study is to study the contribution of compensation, morale and the environment to the performance of employees at the Roudlotut Tholibin Balen Bojonegoro Islamic Boarding School Foundation. In addition to analyzing the independent variables (compensation, spirit of work and work environment) on the agreed variables (employee performance). The sampling technique in this study used nonprobability sampling design, namely by using purposive sampling, from the participation of 102 permanent employees, the sample used was 76 employees with at least a bachelor's degree. The results showed partial compensation, spirit of work and work environment had a significant positive effect on employee performance, and stated compensation, spirit of work and work environment together had a significant influence on employee performance. Compensation decisions that greatly affect employees are benefits / bonuses or other incentives (if any) obtained in accordance with the applicable provisions. Based on the results of the study, morale and the environment have a positive significance for performance. As a test score t the work environment is greater than compensation and spirit of work, so the work environment is more dominant on performance.